1994
DOI: 10.1021/bi00250a003
|View full text |Cite
|
Sign up to set email alerts
|

New type of linkage between a carbohydrate and a protein: C-glycosylation of a specific tryptophan residue in human RNase Us

Abstract: We report a new type of linkage between a carbohydrate and a protein, involving the rarely modified side chain of a tryptophan residue. An aldohexopyranosyl residue was found to be linked via a C-C bond to the indole ring of the tryptophan residue at position 7 of human RNase Us. Mass spectrometric analysis of peptides containing this residue showed a molecular mass 162 Da higher than that expected for tryptophan. The fragmentation pattern of the modified amino acid side chain was reminiscent of that of aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
235
3
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 270 publications
(246 citation statements)
references
References 43 publications
7
235
3
1
Order By: Relevance
“…Furthermore, digestion of the thermolytic peptide with elastase yielded the peptides 5-8 and 9-10, whose absorbance ratio at 280 nm was 1.62 and 1.58, for the peptides obtained from hp-and lp-RNase 2, respectively. The value of this ratio was in good agreement with the one previously found for C-mannosylated and unmodified Trp, i.e., 1.56 (Hofsteenge et al, 1994), which suggests that the peptides from both proteins are identical and also that Trp-7 in the peptide from hp-RNase 2 is modified.…”
Section: Stability Of the O-mannosylated Syntheticsupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, digestion of the thermolytic peptide with elastase yielded the peptides 5-8 and 9-10, whose absorbance ratio at 280 nm was 1.62 and 1.58, for the peptides obtained from hp-and lp-RNase 2, respectively. The value of this ratio was in good agreement with the one previously found for C-mannosylated and unmodified Trp, i.e., 1.56 (Hofsteenge et al, 1994), which suggests that the peptides from both proteins are identical and also that Trp-7 in the peptide from hp-RNase 2 is modified.…”
Section: Stability Of the O-mannosylated Syntheticsupporting
confidence: 90%
“…Recently, it was found that Trp-7 in human RNase 2 1 is modified by C-glycosidic attachment of an R-mannosyl residue (Hofsteenge et al, 1994;de Beer et al, 1995). In contrast to the previously known N-and O-glycosidic linkages to asparagine and serine, or threonine, the mannopyranosyl C1′ atom is in this case directly linked to the C2 atom of the tryptophan indole ring.…”
mentioning
confidence: 88%
See 3 more Smart Citations